2018
DOI: 10.1111/petr.13172
|View full text |Cite
|
Sign up to set email alerts
|

Isolated cutaneous mucormycosis in a pediatric renal transplant recipient

Abstract: Mucormycosis is a rare and potentially life-threatening infection, typically affecting immunocompromised hosts. We report a case of an adolescent boy who developed primary isolated cutaneous mucormycosis in the early period following kidney transplantation. Surgical excision was performed using intraoperative fungal staining to obtain clear margins, followed by topical and systemic antifungal therapy. A skin graft was then applied to the excised area with good healing, and the patient made a full recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We have observed that wound margins may appear clinically and histologically intact while still having viable organisms present. We therefore have used a system of intraoperative assessment of resected tissue margins sent by the surgical team to the clinical microbiology laboratory for fluorescent microscopy using calcofluor wet mounts [40,41].…”
Section: Principles Of Managementmentioning
confidence: 99%
“…We have observed that wound margins may appear clinically and histologically intact while still having viable organisms present. We therefore have used a system of intraoperative assessment of resected tissue margins sent by the surgical team to the clinical microbiology laboratory for fluorescent microscopy using calcofluor wet mounts [40,41].…”
Section: Principles Of Managementmentioning
confidence: 99%
“…Intra operative frozen sections can be used and histopathological examination can be done to confirm adequate excision, however the sensitivity of frozen section is only around 68.4%. 10 Both our patients did not undergo intra-op frozen section. They underwent debridement until all subcutaneous necrotic tissue was removed, following which they underwent wound closure using rotational flap and split skin grafting techniques.…”
Section: Discussionmentioning
confidence: 89%
“…Intraoperative assessment of margins by fluorescent microscopy has been advocated for that. 18 Medical management includes use of antifungal drugs. Liposomal amphotericin B (LAB) is the drug of choice and the dose should be at least 5 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%